Strategi Program CSR Rumah BUMN PT Bank Mandiri Tbk: Case study on the CSR program of PT Bank Mandiri Tbk - Fadhel Adyra Nugraha; Dr. Dadan Mulyana, Drs., M.Si (Bandung Conference Series: Public Relations, 2023)
Abstract. PT Bank Mandiri implements this Corporate Social Responsibility as a form of program to advance the community's economy. From PT Bank Mandiri's Corporate Social Responsibility, researchers see the function of Public Relations as a bridge from the company to establish relationships with the public. This research aims to find out how PT Bank Mandiri maintains effectiveness in the BUMN House program, to find out how the partnership development carried out by PT Bank Mandiri in the BUMN House program, and to find out the reasons why PT Bank Mandiri collaborates with external stakeholders for the success of its program. This research uses the theories of Public Relations, Corporate Social Responsibility, and Stakeholders Relations. The methodology used for this research is a qualitative method with a case study approach to the BUMN House program of Bank Mandiri Tbk. Data were collected through in-depth interviews, observation, documentation methods and literature review. The data validity test in this study used data source triangulation. The results of this study found that Rumah BUMN maintains the effectiveness of its program through partnerships, evaluation, transparency, and collaboration. It was found that Rumah BUMN established strategic partnerships with MSME players. Through this collaboration, Rumah BUMN supports MSMEs with financial support, training and market access, which drives local economic growth and has a positive social impact. Then to achieve broader social impact, multinational companies leverage their knowledge, resources, and networks. This cooperation enhances sustainable CSR programs, increases the company's credibility, and generates sustainable benefits for society and its stakeholders. Abstrak. PT Bank Mandiri menerapkan Corporate Social Responsibility ini sebagai bentuk program untuk memajukan ekonomi masyarakat. Dari Corporate Social Responsibility PT Bank Mandiri peneliti melihat fungsi dari Public Relations sebagai jembatan dari perusahaan untuk menjalin hubungan dengan publik. Penelitian ini bertujuan untuk mengetahui bagaimana PT Bank Mandiri menjaga efektivitas dalam program Rumah BUMN, untuk mengetahui bagaimana pengembangan kemitraan yang dilakukan PT Bank Mandiri dalam program Rumah BUMN, dan untuk mengetahui alasan mengapa PT Bank Mandiri menjalin kerja sama dengan stakeholders external untuk keberhasilan programnya. Dalam penelitian ini menggunakan teori Public Relations, Corporate Social Responsibility, dan Stakeholders Relations. Metodologi yang digunakan untuk penelitian ini adalah metode kualititatif dengan pendekatan studi kasus pada program Rumah BUMN Bank Mandiri Tbk. Data dikumpulkan melalui wawancara mendalam, observasi, metode dokumentasi dan kajian pustaka. Uji keabsahan data pada penelitian ini menggunakan triangulasi sumber data. Hasil dari penelitian ini diperoleh bahwa Rumah BUMN menjaga efektifitas programnya melalui kemitraan, evaluasi, transparansi, dan kolaborasi. Lalu ditemukan Rumah BUMN menjalin kemitraan strategis dengan pelaku UMKM. Melalui kolaborasi ini, Rumah BUMN mendukung UMKM dengan dukungan keuangan, pelatihan, dan akses pasar, yang mendorong pertumbuhan ekonomi lokal dan memiliki dampak sosial yang positif. Lalu untuk mencapai dampak sosial yang lebih luas, perusahaan multinasional memanfaatkan pengetahuan, sumber daya, dan jaringan yang tersedia. Kerja sama ini meningkatkan program CSR yang berkelanjutan, meningkatkan kredibilitas perusahaan, dan menghasilkan keuntungan yang berkelanjutan bagi masyarakat dan pemangku kepentingannya.